The influence of Discount Framing towards Brand Reputation and Brand Image on Purchase Intention in Somethinc Products at Shopee - Khanza Zhafira, Ades; Sigit, Murwanto (Publisher Cv. Inara, 2023)
The large number of internet users supports the increase in electronic commerce or ecommerce in Indonesia. One of the e-commerce that has many enthusiasts and dominates the market in Indonesia is Shopee. The purpose of this research is to examine the impact of discount framing on purchase intention which is mediated by brand reputation and brand image. Data collection in this study was carried out using the Google form and questionnaires distributed online. The methodology applied uses a quantitative approach with a purposive sampling technique. Researchers conducted a quantitative study with 170 samples of valid data obtained from respondents in Indonesia who are Shopee e-commerce users. Data management uses SPSS and PLSSEM (smartPLS) applications. The variables used in this research are discount framing, brand reputation, brand image, and purchase intention. The results of this study state that discount framing has a positive influence towards brand reputation and brand image on Purchase Intention in Somethinc Products at Shopee.